Bacterial dynamics and functions driven by a novel microbial agent to promote kitchen waste composting and reduce environmental burden. (20th February 2022) - Wang, Can; Wu, Minghui; Peng, Chuanhai; Yan, Fangfang; Jia, Yinxue; Li, Xing; Li, Mingxing; Wu, Bin; Xu, Heng; Qiu, Zhongping
Abstract: Due to high oil content and complex composition, Kitchen waste (KW) is refractory for biotreatment and easily causes environmental burden, especially in Sichuan area with greasy cooking habits. To facilitate KW composting, a nitrogen-retaining & decomposing-promoting microbial agent (NRDPMA) was constituted with functional bacteria to decompose refractory substances, retain nutrients, and reduce gas emission. With NRDPMA, high-temperature period was achieved 2 days earlier and extended by 6 days, shorting the process by 15 days. 36.57% less NH3 and 22.30% less H2 S were released. The total nitrogen of the compost product was increased by 17.14%. Functional bacteria in NRDPMA (e. g. Bacillus, Pseudomonas, and Oceanobacillus ) displayed obvious advantages throughout composting, which reshaped microbial community composition and drove material transformation. PICRUST2 prediction confirmed a higher gene occurrence related to metabolism of lipid, lignocellulose, and nitrogen. The great decomposing and transformation capacity made NRDPMA an alternative to improve the efficiency of composting on recycling such lipid-containing waste. And functional bacteria targeting refractory components should be included for biotreatment of waste. This study should give a new perspective on industrial KW composting. Graphical abstract: Image 1 Highlights: 6 days longer high-temperature period with 36.57% less NH3 and 22.30% less H2 S. NRDPMA conserved 17.14% higher nitrogen with 15 days shorter composting period. Functional bacteria of NRDPMA targeting lipid, starch, and cellulose played a crucial role. NRDPMA participated in all the composting periods, drove microbial community change.